7
$\begingroup$

How do I prove this identity:

$$\frac{\sin x}{x}=\left(\cos\frac{x}{2}\right) \left(\cos\frac{x}{4}\right) \left(\cos \frac{x}{8}\right)...$$

My idea is to let $$y=\frac{\sin x}{x}$$ and $$xy=\sin x$$

Then use the double angle identity $\sin 2x=2\sin x \cos x$ and its half angle counterparts repeatedly. I see some kind of pattern, but I can't seem to make out the pattern and complete the proof.

$\endgroup$

marked as duplicate by Robert Z, Paul Frost, Micah, Lord Shark the Unknown, Nosrati Sep 1 '18 at 17:12

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

9
$\begingroup$

Note the fact that $$ \cos \frac{x}{2^k} = \frac12 \cdot \frac{\sin (2^{1-k} x)}{\sin(2^{-k}x)}, $$ and we have $$ \prod_{k = 1}^n \cos \frac{x}{2^k} = \frac{1}{2^n} \cdot \frac{\sin x}{\sin(2^{-n}x)} = \frac{2^{-n}x}{\sin(2^{-n}x)} \cdot \frac{\sin x}{x}. $$ For all $x$, as $n \to \infty$, we have $$ \lim_{n \to \infty} \prod_{k = 1}^n \cos \frac{x}{2^k}= \frac{\sin x}{x} \cdot\lim_{n \to \infty} \frac{2^{-n}x}{\sin(2^{-n}x)} = \frac{\sin x}{x}. $$

$\endgroup$
  • 2
    $\begingroup$ May I ask you to give me some about the first fact. It is very nice! Regards $\endgroup$ – mrs Sep 1 '18 at 6:43
  • 1
    $\begingroup$ For the first fact, let $y=x/2^k$, see it is just the double angle formula. $\endgroup$ – DanielV Sep 1 '18 at 7:11
  • $\begingroup$ clever starting point (+1)! $\endgroup$ – G Cab Sep 1 '18 at 15:32
0
$\begingroup$

Partial answer:

The Taylor series of $\sin x$ is $x - \frac{x^3}{3!} + \frac{x^5}{5!} \cdots$, so:

$$\frac{\sin x}{x} = 1 - \frac{x^2}{3!}+\frac{x^4}{5!} \cdots.$$

Meanwhile, $\cos x = 1 - \frac{x^2}{2!} + \frac{x^4}{4!}$, and therefore:

$$\cos(\frac{x}{2^1}) = 1 - \frac{x^2}{2^2 \cdot 2!} + \frac{x^4}{2^4 \cdot 4!} - \frac{x^6}{2^6 \cdot 6!} \cdots$$

$$\cos(\frac{x}{2^2}) = 1 - \frac{x^2}{2^4 \cdot 2!} + \frac{x^4}{2^8 \cdot 4!} - \frac{x^6}{2^{12} \cdot 6!} \cdots$$

$$\cos(\frac{x}{2^3}) = 1 - \frac{x^2}{2^6 \cdot 2!} + \frac{x^4}{2^{12}\cdot 4!} - \frac{x^6}{2^{18} \cdot 6!} \cdots$$

and so on.

The constant term of the infinite product is $1$.

There is only one way to make an $x^2$ term: by multiplying the constant and the $x^2$ term. The coefficient of the $x^2$ term is:

$$-\frac{1}{2^2 \cdot 2!} - \frac{1}{2^4 \cdot 2!} - \frac{1}{2^6 \cdot 2!},$$

which is a geometric series with $a = \frac{1}{8}$, and $r = \frac{1}{4}$, which the formula gives as $\frac{\frac{1}{8}}{1- \frac{1}{4}} = \frac{1}{6}$.

$\endgroup$

Not the answer you're looking for? Browse other questions tagged or ask your own question.